PENGARUH SARANA PRASARANA dan KUALITAS PELAYANAN ADMINISTRASI DINAS KEPENDUDUKAN dan PENCATATAN SIPIL TERHADAP KEPUASAN MASYARAKAT - Mella Alkhori Datus Salam; Brillian Rosy (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
This study aims to determine the effect of infrastructure on community satisfaction, the effect of service quality on community satisfaction and the effect of infrastructure and service quality together on community satisfaction. The type of research used is descriptive research through a quantitative approach with data collection techniques through questionnaires and the data analysis technique used is multiple linear regression with the help of SPSS version 26 application. The results of the study draw conclusions based on the t test, infrastructure (X1) has an effect on community satisfaction (Y). Service quality (X2) has an effect on community satisfaction (Y). Furthermore, based on the results of the simultaneous test obtained F count of 193,058 with a probability value of 0.000 <0.05. So it can be concluded that simultaneously the variables of infrastructure (X1) and service quality (X2) have a direct influence on the variable of community satisfaction (Y). Based on the results of the study, it is hoped that the Disdukcapil office employees can increase the availability of good and decent facilities and infrastructure and service quality in order to create better community satisfaction and hope that further research can add other variables, so that research can be more accurate.